(untitled) (Bangladesh Journal of Medical Science, 2011)
This article explores the issue of "evaluating goodness in qualitative research", from a perspective of novice qualitative researchers. Despite the recent upsurge in publications of qualitative studies especially in health sciences, the issue of goodness in qualitative research is still debatable. Qualitative researches in contrast to traditional research not only differ in research methodology and methods but also in data analysis. Although approaches for evaluating goodness in qualitative research are available but consensus on universality is still lacking. The development of extrinsic criteria although provide the guidelines for post positivist studies, however, it is not acceptable to interpretivist /constructivist who believe on multiple realities and knowledge as co construct. The authenticity criteria although fits well to constructivism/interpretivism, however, researchers argue that because it provide a post hoc strategy for evaluation of a study and avoid focusing during its conduct, thus causing serious threats to the credibility. Primary criteria forwarded by Whitemoore et al., although seems essential for all qualitative inquiry but because based on validity has been rejected by authors on the grounds that qualitative epistemological and ontological assumptions are entirely different to the traditional qualitative research. The criteria by Ballinger in 2006 although seems practical in application to all paradigms, however, as it also questions reflexivity which seems irrelevant in realist tradition. Further other general criteria such as seems popular because of its simplistic approach but do not address the terms of ontology, epistemology and paradigm that seem very important in qualitative research. It is important for the novice qualitative researchers to be aware of the debate on the issue of evaluating goodness of qualitative research. However, they should adopt a cautious stand while favouring or rejecting one criteria. Finally the development of a universal and uniform criteria is although important but not necessary requirement for the qualitative research progress. DOI: 10.3329/bjms.v10i1.7314 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.11-20